Benarkah Hamba Ketiga Malas dan Jahat? - Carel Hot Asi Siburian (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
The “classical” reading of Matthew 25:14-30 has always referred to the third servant as being unfaithful to his master and to what his master entrusted to him. “Talents” are always considered as “gifts” given by God that must always be developed by human. This reading also “seems” to negate the objections that appear in the text, when the third servant gives resistance to the master. But does this parable really show that the third servant is lazy and wicked, and does it really “only” speak of God’s gift? This paper will present a critical-alternative reading of Matthew 25:14-30. Using the narrative approach method, there are at least four readings of this parable, which are (1) Jesus is/was doing the third servant; (2) the third servant is a good servant; (3) this parable is not about gifts; and the possibility that (4) Matthew’s Gospel is “hiding” something; that the answer to the parable in Matthew 25:14-30 is in Matthew 25:31-46. That is why the parable of the talents must be read together with the story of the last judgement.